PEMBUATAN GRANUL JAMU KUNYIT ASAM SEBAGAI ANTIOKSIDAN ALAMI DI DESA KALITENGAH TANGGULANGIN SIDOARJO - Panji Ratih Suci; Erna Fitriany; Zuanta Pangestutik; Andri Priyoherianto; Fahmi Ardianti Purnawiranita (Jurnal Pengabdian IKIFA, 2025)
Turmeric is a type of rhizome that contains secondary metabolites that have antioxidant activity. Generally, turmeric is processed into spices or as raw material for herbal medicine such as tamarind turmeric herbal medicine. This activity aims to introduce the community in Kalitengah Tanggulangin Village, Sidoarjo, to processing tamarind turmeric granules as a natural antioxidant, involving PKK women from Kalitengah village. Activities The method used during the service process uses a participatory approach consisting of observation, training and evaluation. Questionnaires were given to 49 PKK women respondents. The pretest was carried out before the training was carried out, and continued with a post-test after the respondents received the training and tried instant turmeric powder for themselves. Evaluation results based on respondents' answers to the questionnaire given showed an increase in knowledge related to tamarind turmeric by 100%, knowledge of the benefits of turmeric by 81.6%, knowledge about granules by 81.6% and readiness to take part in training increased by 98%. These results show that this training had a positive impact on PKK mothers in Kalitengah village, Sidoarjo